Tipologi Metode Pendidikan Tauhid di Pondok Pesantren Al-Amien Purwokerto Wetan - Mochammad Sidqi Awaliya Rahman; M. Misbah (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2022)
This study aims to determine the variety of monotheism education receptions that are expressed through several learning methods and the meaning behind them. This research was conducted using a qualitative method, and includes field research. In obtaining data, researchers used various instruments, such as interviews, observations, and documentation. Analysis in this study by means of data reduction, data display, and drawing conclusions. From this study, it was found that (1) the variety of al-Qur'an receptions at Al-Amien Islamic Boarding School included; (a) exegesis reception (lecture method), through recitation of the book of monotheism; (b) aesthetic reception (inquiry method), through the placement of calligraphy verses of the Qur'an; (c) functional reception (AIR method), through reading shalawat jibril and nadham aqidatul awwam. (2) Among the binding meanings in each form of reception are; (a) objective meaning, as a form of obedience, preserving tradition, and increasing will; (b) expressive meaning, as a form of scientific deepening of monotheism, increasing awareness of diversity, and serenity; (c) documentary meaning, as a form of local visualization of a comprehensive culture.